Predictors of in-hospital mortality in patients with acute myocardial infarction due to unprotected left main trunk lesion: insight from the Tokyo Cardiovascular Care Unit network multicenter registry. (25th November 2020) - Mitsuhashi, Y; Tanaka, H; Saji, M; Miyachi, H; Yamamoto, T; Nagao, K; Takayama, M
Abstract: Background: Acute myocardial infarction (AMI) due to unprotected left main trunk (LMT) lesion remains a clinical challenge because it requires prompt and efficient revascularization in catastrophic clinical presentation. However, predictors of in-hospital prognosis in patients with LMT-AMI are still not fully understood. Purpose: To examine the predictors of in-hospital mortality in patients with LMT-AMI. Methods: From 20, 257 AMI patients in the Tokyo Cardiovascular Care Unit network registry (comprising 72 hospitals) from 2013 to 2017, we identified 371 (1.8%) eligible LMT-AMI patients without a history of coronary artery bypass grafting (CABG) and divided them into two groups: 254 survivors and 117 non-survivors. Measured variables included patient demographics, vital signs, laboratory data on admission, and in-hospital treatment. The outcome was in-hospital mortality. We performed a multivariable logistic regression analysis for in-hospital mortality with adjustment for the following 9 potential confounders, based on previous studies: (1) age, (2) sex, (3) Killip class, (4) ST elevation, (5) wide QRS (>120 msec), (6) the Thrombolysis in Myocardial Infarction (TIMI) grade on initial coronary angiography, (7) number of vessels with significant stenosis other than LMT, (8) renal dysfunction on admission, and (9) plasma glucose on admission. Results: Overall, mean age was 70.6±11.8 years and 81.9% were male. ST-elevation myocardial infarction accounted for 61.8%. Cardiac arrest was observed in 102 (33.6%) patients. Percutaneous coronary intervention and CABG were performed in 302 (81.8%) and 63 (17.0%) patients, respectively. Intra-aortic balloon pumping and veno-arterial extracorporeal membranous oxygenation were used in 288 (77.8%) and 81 (21.9%) patients, respectively. In-hospital mortality was 31.5%. Multivariable logistic regression analysis showed that higher in-hospital mortality was significantly associated with Killip class IV (adjusted odds ratio 3.41 [95% confidence interval 1.36–8.56]; reference: Killip I), TIMI grade 0 (3.51 [1.22–10.14]; reference: TIMI grade 3), renal dysfunction (estimated glomerular filtration <60 mL/min/1.73m 2 ; 6.48 [2.53–16.57]), and high plasma glucose on admission (>150 mg/dl; 3.64 [1.33–9.97]). Age, sex, ST-elevation, wide QRS, and multi-vessel disease were not significantly associated with in-hospital mortality. Conclusions: LMT-AMI remains life-threatening in the current era of widely available revascularization. Our results showed that haemodynamic compromise, no coronary flow, renal dysfunction, and high plasma glucose on admission were strong predictors of in-hospital mortality after LMT-AMI. Given the high cardiac arrest rate, more aggressive therapeutic measures including mechanical circulatory support may be required to improve the prognosis of LMT-AMI. Funding Acknowledgement: Type of funding source: None